Language Impairments in Youths With Traumatic Brain Injury: Implications for Participation in Criminal Proceedings. Issue 2 (March 2015) - Wszalek, Joseph A.; Turkstra, Lyn S.
Abstract : As many as 30% of incarcerated juveniles have a history of traumatic brain injury (TBI). Moderate or severe TBI is associated with a high risk of impairment in language comprehension and expression, which may have profound effects on juveniles' ability to understand and express themselves in criminal proceedings. In this article, we review common language impairments in youths with TBI and discuss potential effects of these impairments on 3 stages of US criminal proceedings: (1) initial encounter with law enforcement; (2) interrogation and Miranda rights; and (3) competence to undergo trial proceedings. We then describe language assessment tools and procedures that may be helpful in legal contexts. Our aim was to inform clinicians and legal staff working with juvenile defendants with TBI, with the long-term goal of developing empirically based guidelines to ensure that juvenile defendants with TBI can fully and effectively participate in criminal proceedings.